Model matematika kecanduan lem aibon pada anak jalanan dengan faktor edukasi dan treatment - Yeni, Tiya Enggri; Ahmad, Defri (Journal of Mathematics UNP, 2024)
Abuse of aibon glue will cause addictive behavior because there is substance lysergic acid diethyilamide in the glue. The level of spread of Aibon glue addiction depends on educational factors and the tratment given. This study aims to establish, analyze and interpret the results of the analysis of the mathematical model of Aibon glue addiction in street children with education and treatment faktors. This research includes basic research using descriptive methods. The mathematical model formed is the SEIR model. Based on the analysis that has been carried out, two fixed points are obtained, namely the disease-free fixed point and the endemic fixed point. Disease-free fixed point is asymptotically stable if  Whereas for an endemic fixed point it will be asymtotically stable if it meets the requirement obtained from the Routh-Hurwitz criteria. The greater the education given, the more educated the population will be. Whereas when the treatment is getting bigger, the infected population decreases.